The problem of Germany : an interim report by a Chatham House study group. (London New York Toronto Bombay Melbourne Cape Town : The Royal Institute of International Affairs Oxford University Press, 1943)
Bibliotheek Camille Huysmans
Engels
Monografie
Keywords: Wereldoorlog 2; Naoorlogse Politiek; Duitsland